Analyzing the Impact of Consumer Confidence Index and Geopolitical Risk Indices on Foreign Trade in Food Commodities: Evidence from Turkey - GÜRSOY , Samet; KARABULUT, Ali Naci; Bulut, Zeki Atıl (International Journal of Contemporary Economics and Administrative Sciences, 2023)
In recent years, the increase in global crises in areas such as climate, food, health, and international relations has led to an increase in the level of interest of both economists and senior managers in macroeconomic indicators. In this context, the consumer confidence index and the geopolitical risk index have become increasingly popular in both econometric analyses and academic discussions. In this study, the effects of consumer confidence and geopolitical risk indices on food imports and exports in Turkey for the period between January 2013 and January 2021 were analyzed through symmetric and asymmetric causality analyses. The consistent results of the Toda Yamamoto causality and Hatemi-j asymmetric causality tests indicated that a decrease in the consumer confidence index in Turkey leads to a decrease in exports of processed food goods and an increase in geopolitical risk leads to an increase in imports of unprocessed food goods.